2018
DOI: 10.4012/dmj.2017-008
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblasts preferentially adhere to peaks on micro-structured titanium

Abstract: The aim of the study was to investigate cell adhesion to micro-structured titanium. Osteoblastic MC3T3 cells were cultured on smooth (P) or sand-blasted/acid-etched (SLA) titanium discs and were observed at scanning electron microscope/focused ion beam (SEM/ FIB). Myosin II and actin microfilaments were labelled for epifluorescence microscopy. FIB revealed that cell adhesion initiated centrally and expanded to the cell periphery and that cells attached on the substrate by bridging over the titanium irregularit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 30 publications
5
19
2
Order By: Relevance
“…Low cytotoxicity and high proliferation rates are imperative for an optimal implant material and are heavily influenced by the surface properties (Ross, Jiang, Bastmeyer, & Lahann, ). As expected from numerous studies involving smooth as well as structured commercially pure titanium and Ti6Al4V (Anselme et al, ; Deligianni et al, ; Lagonegro et al, ), we confirmed that the initial cytotoxicity was low (<10%) on smooth control surfaces and even lower on EB surfaces (<6%), proving optimal cytocompatibility of proposed surfaces according to ISO 10993‐5. Proliferation was comparable among all tested surfaces and increased over the tested time span of 10 days.…”
Section: Discussionsupporting
confidence: 89%
“…Low cytotoxicity and high proliferation rates are imperative for an optimal implant material and are heavily influenced by the surface properties (Ross, Jiang, Bastmeyer, & Lahann, ). As expected from numerous studies involving smooth as well as structured commercially pure titanium and Ti6Al4V (Anselme et al, ; Deligianni et al, ; Lagonegro et al, ), we confirmed that the initial cytotoxicity was low (<10%) on smooth control surfaces and even lower on EB surfaces (<6%), proving optimal cytocompatibility of proposed surfaces according to ISO 10993‐5. Proliferation was comparable among all tested surfaces and increased over the tested time span of 10 days.…”
Section: Discussionsupporting
confidence: 89%
“…hexagon-wide podosomes, which were not observed at earlier time-points, became visible around the cell body, beside lamellipodia ( Figure 3F; Figure 4F). FIB analysis of 3.6 and 4.0 surfaces at 48 h ( Figure 6) showed, however, that the cell body, where intracellular tension was arguably higher, was stretched over the pillars, without entering the space in between the pillars ( Figure 6B or Figure 6E), similarly to what we observed with SLA surfaces [20] and unlike the peripheral septs that can even cover whole pillars. The higher tension attained in the cytoplasm of the cell body is indirectly confirmed by its thinness, as the shape of the underlying pillars can be guessed through the cytoplasm ( Figure 6C or Figure 6E).…”
Section: Sem Morphologysupporting
confidence: 69%
“…To better understand cell morphology on biomaterials, new instruments have been developed, such as the Focused Ion Beam Microscope, which combines a Scanning Electron Microscope with a Gallium ion beam that can cut through samples, through minimal manipulation, and allow for close examination of their conformation [20]. The present study relied on such microscopy tools to investigate how hexagonal micro-patterned substrates affect the behavior of murine calvaria MC3T3 osteoblastic cells, a well-known model for bone cells that is capable of mimicking many physiological features of normal osteoblasts [21].…”
Section: Introductionmentioning
confidence: 99%
“…The arrangements of the cells on this last surface were elongated projections of the cytoplasm that followed the surface of the peaks and avoided the valleys of the surface. They showed that when cells grow on microtextured substrates, such as SLA, its adhesion area is limited to the Ti peaks of the surface and the surface areas near the peaks, and the cell bodies join over the valleys of the surface [50].…”
Section: Discussionmentioning
confidence: 99%